Localization of Industry and Vertical Disintegration - Holmes, Thomas J. (The Review of Economics and Statistics, 1999)
Theory suggests that vertical disintegration should be greater in areas where industries localize. This paper provides some evidence that this implication is true for the U.S. manufacturing sector. Purchased inputs as a percent of the value of output is used as a measure of vertical disintegration. To measure the localization of industry, for each manufacturing plant the amount of employment in neighboring plants in the same industry is determined.